Evaluasi Pengukuran Kinerja dengan Pendekatan Balance Scorecard (Studi pada PT BNI (Persero), Tbk.) - Jana Sandra (Majalah Ilmiah Bijak, 2018)
This case study is a performance measurement system on BNI with PMS (performance measuring system) method is a Balance Scorecard based. Since 2006, BNI's performance measurement system uses only 2 perspectives, namely financial and operational, so it has not presented the comprehensive and integrative performance of the organization. However, starting in 2011, BNI performs Balance Scorecard based performance process using 6 (six) perspectives namely: financial, growth, risk, customer, employee and process. Performance measurement is conducted at 6 (six) level of organization that is: BNI wide, sectoral, division, region, branch and center while for office service and cash office level measurements are still in developmen process. With the development of six perspectives and measurement of all levels, it is expected that BNI performance measurement becomes more objective and linkage. BNI wide performance measurement results at the end of each year with a balanced scorecard approach is expected to be a strategic planning of the bank in determining the performance improvement of the current year so that the scorecard can be maximized.